ACCESS CONTROL METHOD AND APPARATUS BASED ON CLOUD COMPUTING TECHNOLOGY - LIU, Boyang; LI, Jun; LIN, Weibo (2024)
An access control method based on cloud computing technology. The method comprises: a request initiator deployed on a cloud sending an access request to a third-party service, wherein the access request carries subject attribute information and environment attribute information of the request initiator, the subject attribute information indicates identity information of the request initiator on the cloud, and the environment attribute information indicates environment information of the request initiator on the cloud; the third-party service receiving the access request; and the third-party service extracting the subject attribute information and the environment attribute information from the access request, wherein the subject attribute information and the environment attribute information are used for calculation with an access control policy, so as to determine whether the third-party service allows or refuses the access request. In the access control method provided in the present application, a subject a